Optimization of Interferon–Alpha and Imatinib Combination Therapy for Chronic Myeloid Leukemia: A Modeling Approach. Issue 1 (18th October 2018) - Bunimovich‐Mendrazitsky, Svetlana; Kronik, Natalie; Vainstein, Vladimir
Abstract: Chronic myeloid leukemia (CML) in its chronic phase is treated with imatinib, with an attempt at discontinuation after at least three years of therapy in patients with deep molecular responses. Following the attempted discontinuation, approximately half of the patients regress and need to return to the imatinib treatment. Interferon‐alpha monotherapy results in a cure in only a small percentage of patients. The combination of both drugs is simulated to optimize the treatment with respect to duration and schedule. This is achieved through a mathematical model in which three cell types are described: leukemic stem cells, mature leukemic cells, and CML‐cytotoxic‐lymphocyte (CML‐CTL) cells. The model is simulated in silico, under different combination treatment regimens of imatinib and interferon‐alpha. It is observed that a low level of CML‐CTL cells causes failure of the combination treatment; an intermediate level of CML‐CTL produces mixed results for the success of the combination treatment; a high level of CML‐CTL cells promotes the success of the combination treatment. According to the model, treatment can lead to low‐level persistence of CML stem cells after treatment discontinuation, even in the absence of acquired drug resistance. The model defines conditions under which imatinib‐interferon‐alpha treatment leads to CML eradication. Abstract : Chronic myeloid leukemia (CML) is treated with imatinib with an attempt at discontinuation after two years . Following this attempt, half of the patients regress and need to return to the treatment. Here, a computational model shows that the addition of interferon to imatinib for 52 weeks increases the rate of eradication of CML stem cells. The model shows the most important variable for eradication is the amount of CML‐specific cytotoxic T cells.